DEWI SRI SEBAGAI FIGUR IBU MITOLOGIS: TINJAUAN NARASI DAN VISUAL FOLKLOR JAWA TIMUR - F Fitrahayunitisna; I Kadek Yudi Astawan; A. Syarifuddin Rahman (Jurnal Tradisi Lisan Nusantara, 2022)
Dewi Sri is a character in Javanese mythology. This goddess is close to the Javanese community, especially the farming community. Dewi Sri as the goddess of rice is widely written in ancient literature as well as in oral literature (folklore). In practice, Dewi Sri is often mentioned in traditional rituals and beliefs of the Javanese people. The cult of Dewi Sri is proof of the existence of a deity in the form of mother in the belief system of patriarchal Javanese society. The research on Dewi Sri as a mythological mother figure is important as a source of creating works of art or digital literature based on local wisdom. So, the focuses of this research is to find the character of Dewi Sri based on narratives and visual review and to analyse Dewi Sri as a mythological mother. This is a qualitative research with a social representation approach. The data is in the form of text or verbal speech. Sources of data are the people of East Java. Data collected by interview and literature study. The result shows that Dewi Sri has a feminine character as the positive mother archetype in Jung's concept. Visually, Dewi Sri is depicted with feminine symbols of adult women, which is visually different from the ancient art works. Meanwhile, the divine figure of Dewi Sri that found was a mythological mother and spiritual figure with a feminine opposition as "Mother Goddess". Javanese belief that Dewi Sri gives bless with fertility. The conclusion is that figure of Dewi Sri can be used as a source of creating art and literature based on local wisdom.